First principles investigation on the nitrogen-doped planar aluminene for hydrogen storage application. Issue 1 (March 2020) - Pedrosa, G R; Villagracia, A R; Bayasen, D S; Lin, H; Ong, H L; David, M; Arboleda, N
Abstract: With the rise of carbon emission daily, a pursuit for cleaner energy such as hydrogen fuel is necessary. Obtaining a good hydrogen storage is one of the main bottleneck to achieve a working hydrogen economy. Materials including two-dimensional systems have been widely investigated for potential hydrogen storage. In this work, the effects of nitrogen on the hydrogen adsorption on planar hexagonal aluminene was studied using density functional theory. Aluminene was decorated with nitrogen at different sites: top, hollow and bridge. Results showed that nitrogen was adsorbed at the top, bridge and hollow sites at a distance of 0.00Å to 1.80 Å with binding energies of 2.71 eV, 4.88 eV, and 3.44 eV, respectively. Comparing to the pristine aluminene, there was no major difference with its electronic and magnetic properties based on the density of states of the nitrogen-doped aluminene while the nitrogen atom gained some charges from the aluminium atoms based on the charge difference. On the other hand, a hydrogen molecule was adsorbed with binding energies ranging from 13.4meV to 26.3 meV close enough to the adatom on the decorated system. Minimal broadening of energy level was found from the density of states. This work shows that aluminene with nitrogen impurity can adsorb hydrogen molecules. However, high concentration of nitrogen will lower the hydrogen capacity of aluminene.